Drug resistance mechanisms in Mycobacterium tuberculosis infection and challenges in vaccine development - Zhang, Shuying; Cheng, Juan; Tang, Yuanyuan (Frontiers in Pharmacology, 2026)
Drug-resistant Mycobacterium tuberculosis(Mtb) has become a global public health crisis, and its diverse drug resistance jointly reduces the effectiveness of antibacterial drugs. Mtb resistance is not merely genetic but involves a synergistic interplay of cell wall remodeling, metabolic reprogramming, and epigenetic regulation, all of which are closely linked to its capacity for immune evasion. These mechanisms lead to the failure of traditional treatments, exacerbating the prolongation of treatment duration, the increase in mortality rate and the spread of drug-resistant bacteria. Vaccine research has gradually become a key strategy for preventing and controlling the spread of drug-resistant tuberculosis. This review synthesizes these multifaceted resistance pathways and parallels them with the challenges in vaccine development, highlighting the limited efficacy of Bacillus Calmette-Guérin and the promise of next-generation candidates. It further explores the landscape of novel therapeutic strategies, including new drugs like bedaquiline and host-directed therapies. In the future, efforts should be focused on the development of multivalent vaccines, the integration of chemoimmunotherapy, and the sharing of global monitoring data to contribute to the ultimate goal of eliminating tuberculosis.